Profil Kompetensi Science Technology Engginering Mathematic with Pedagogical Content Knowledge Guru Gen Z dan Milenial di Kalimantan Barat - Egy Abdi; Anwar Deli; Afandi Afandi; Indri Astuti (SAP (Susunan Artikel Pendidikan), 2022)
This study aimed to identify STEM PCK competence and barometer for gen z and millennial teachers in West Kalimantan as the authority successor subject in the future education with an evaluation stage which was expected as a further step taken so that progression scale realized and had implications for education advancement, especially in West Kalimantan. Respondents involved in this study amounted to 41 teachers aged 23 to 30 years spread over 14 districts/cities in West Kalimantan applying probability sampling technique. The instrument used is STEM PCK questionnaire adopted from Yildirim and Sahin (2019) which consists of 56 statements consisting of 12 statements related to pedagogy, 14 statements of 21st century skills knowledge, and 30 other questions related to STEM PCK knowledge, the data obtained through the use of a Likert rating scale, then each respondent will be classified into 3 levels, namely high, medium and low using the interpretation of the average score on the Likert scale. The result showed that in general there are 5 respondents or 12.2% who are in the high category and 36 other respondents or 87.8% are in the low category, and there are no respondents who are in the low category, it can be interpreted that although there is no respondents who had low STEM PCK competence, however, there are many millennial teachers in West Kalimantan on a medium scale who are needed to be able to implement every aspect of STEM PCK in learning optimally so that dynamic educational standards are realized with global demands in the modern era.